2021
DOI: 10.22401/anjs.00.5.02
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical-Statistical Study on COVID-19 Cases in Iraq: A Case Study

Abstract: Background: COVID-19 is a disease that started in Wuhan/China in late 2019 and continued through 2020 worldwide.Scientists worldwide continue to research to find vaccines, treatments, and medication for this disease. Studies also conenue to find the pathogenicity and epidemiology mechanisms.Materials and Methods:In this work, we analyzed cases obtained from Alshifaa center in Baghdad/Iraq for 23/2/2020-31/5/2020 with total instances of 797, positive cases of 393, and death cases of 30.Results: Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…This could indicate that women aging 71-80 years have a higher probability to die than males of the same age. In a previous analysis of data obtained from the Alshifaa center; 9 we also concluded that males had a higher tendency to die than females. Our finding was not away from other studies, 6 and the explanation of this occurrence was attributed to the sex hormones and genetic differences.…”
Section: Death Casesmentioning
confidence: 63%
See 3 more Smart Citations
“…This could indicate that women aging 71-80 years have a higher probability to die than males of the same age. In a previous analysis of data obtained from the Alshifaa center; 9 we also concluded that males had a higher tendency to die than females. Our finding was not away from other studies, 6 and the explanation of this occurrence was attributed to the sex hormones and genetic differences.…”
Section: Death Casesmentioning
confidence: 63%
“…Some central laboratories started using the qPCR kits that could detect the positive cases of new strains. [7][8][9] Other than the gene sequencing, Iraq lacks techniques of neutralization techniques, clustered regularly interspaced short palindromic repeats, and CRISPR-associated protein 9 (CRISPR/Cas 9) to detect the virus strains. 25 Instead, Iraq relies on the qPCR as the only technique to detect the virus.…”
Section: Future Perspectivesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, Iraq is still detecting the virus without gene sequencing. Some central laboratories started using qPCR kits to detect the new strain with other positive cases [30][31][32] . The need to sequence SARS-CoV-2 virus isolates is crucial to identify new variants like the U.K. variant.…”
Section: Now Where I S That Strain?mentioning
confidence: 99%